Respuesta :

So the answer would be b=-2. The steps of this is you would refine -2/3 (12b+6) to -4(2b+1) so then the equation would turn into 8-2b= -4 (2b+1). Then you would expand -4(2b+1) into -8b+4. So now the equation is 8-2b=-8b-4. Then you'd subtract 8 from both sides: 8-2b-8=-8b-4-8 which is -2b=-8b-12. Then you'd add 8b to each side. -2b+8b=-8b-12+8b that equals 6b=-12. Then you divide both sides by 6: 6b/6=-12/6. Then you get b= -2. Hope this helped. 
ok so remember you can do anything to an equaiton as long as you do it to both sides

-8-2b=-2/3(12b+6)
distribute so we can work with innter terms
a(b+c)=ab+ac
-2/3(12b+6)=-24b/3-12/3=-8b-4

we now have
8-2b=-8b-4
get all b's on one side
add 8b to both sides
8+8b-2b=8b-8b-4
8+6b=0-4
8+6b=-4
subtract 8 fro both sides
8-8+6b=-4-8
0+6b=-12
6b=-12
divide both sides by 6
6/6b=-12/6
1b=-2
b=-2



b=-2